Studi Literatur Penampilan Reproduksi Sapi Bali Pada Peternakan Sistem Pemeliharaan Semi Intensif Di Daerah Lahan Kering Nusa Tenggara Timur - Imanuel J. Borithnaban; Tarsisius Considus Tophianong; Nancy D. F. K. Foeh (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Bali cattle are native to Indonesia and are derivatives of wild cattle called banteng (Bos bibos or Bos sondaicus) which are found in Ujung Kulon, Java Island and have undergone a process of domestication. In general, the Balinese cattle raising system in NTT can be divided into 3, namely the extensive, intensive and semi-intensive rearing system. The appearance of cattle reproduction represents the quality of the maintenance management that has been carried out. The purpose of preparing this literature study is to determine the reproductive performance of Bali cattle on semi-intensive care farms and to determine age at first calving, days open, pregnancy rate, birth rate, and calving interval of Bali cattle in semi-intensive rearing. This literature study is obtained from collecting various reference sources using the Mendeley and Google Scholar applications. After being analyzed and evaluated, it is obtained that the reproductive performance of Balinese cattle on semi-intensive rearing farms can be seen from high fertility rates, variations in body weight at various levels of age, rearing systems, reproductive management and feeding management and age at first calving, average age at first calving of cows Bali is 1098 ± 12.0 days, days open Bali cattle have an average minimum condition at 121.5 days, the presentation of the pregnancy rate is still low, the percentage of birth rates each year has certain variations and the calving interval of Bali cattle on semi-intensive care farms is an average of 15 to 17 months.